Diverged and Active Partitiviruses in Lichen - Urayama, Syun-ichi; Doi, Nobutaka; Kondo, Fumie; Chiba, Yuto; Takaki, Yoshihiro; Hirai, Miho; Minegishi, Yasutaka; Hagiwara, Daisuke; Nunoura, Takuro (Frontiers in Microbiology, 2020)
The lichen is a microbial consortium that mainly consists of fungi and either algae (Viridiplantae) or cyanobacteria. This structure also contains other bacteria, fungi and viruses. However, RNA virus diversity associated with lichens is still unknown. Here, we analyzed RNA virus diversity in a lichen dominated by fungi and algae using dsRNA-seq technology and revealed that partitiviruses were dominant and active in the microbial consortium. The Partitiviridae sequences found in this study were classified into two genera, which have both plant- and fungi-infecting partitiviruses. This observation suggests that the lichen provides an opportunity for horizontal transfer of these partitiviruses among microbes that form the lichen consortium.Introduction